Preparation and corrosion behavior evaluation of amalgam/titania nano composite - Neda Bahremandi Tolou; Mohammadhossein Fathi; Ahmad Monshi; Vajihesadat Mortazavi; Farzaneh Shirani (Wolters Kluwer Medknow Publications, 2011)
Background: Many attempts have been performed and continued for improvement of dental amalgam properties during last decades. The aim of present research was fabrication and characterization of amalgam/titania nano composite and evaluation of its corrosion behavior. Materials and Methods: In this experimental research, nano particles of titania were added to initial amalgam alloy powder and then, dental amalgam was prepared. In order to investigate the effect of nano particle amounts on properties of dental amalgam, proper amount of 0, 0.5, 1, 2 and 3 wt% of titania nano particles were added to amalgam alloy powder and the prepared composite powder was triturated by a given percent of mercury. X-ray Diffraction, Scanning Electron Microscopy and Energy-Dispersive Spectroscopy techniques were use to characterize the prepared nano composites. Potentiodynamic polarization corrosion tests were performed in the Normal Saline (0.9 wt% NaCl) and Ringer's solutions as electrolytes at 37°C. Immersion corrosion tests were also performed immediately 2 h after preparation of cylindrical samples (4 mm in diameter and 8 mm height) via immersion into a 100 ml volumetric flask consisting of artificial saliva. Results: The results indicated that the current corrosion density of amalgam/titania nano composite changes a bit with adding 1% of nano particles of titania. Also, during the 1 st h after preparation, initial released mercury from prepared nano composite dental amalgam decreased. Conclusion: By adding nano particles of titania and preparing amalgam/titania nano composite as a dental amalgam, corrosion behavior and mercury release during the 2 st h after preparation could be improved.